Pemberian resveratrol oral mencegah peningkatan F2-Isoprostan urin tikus Wistar (Rattus norvegicus) jantan yang dipapar tartrazine - ., Yulyani; Pangkahila, Wimpie; Siswanto, Ferbian M. (UNIVERSITAS SAM RATULANGI, 2017)
Abstract: This study was aimed to prove that oral administration of resveratrol could prevent urinary F2-isoprostane elevation in tartrazine-induced male Wistar rats (Rattus norvegicus). This was an experimental study using the pretest-posttest control group design. Subjects were 24 rats (Rattus norvegicus), Wistar strain, healthy, 2-3 months old, weighing 200-220 g, divided into 2 groups with 12 rats each. The first group (P0), the control group, was given a placebo of 2 ml distilled water 2 hours prior to the administration of tartrazine 75 mg/kg body weight. The second group (P1), the treatment group, was given resveratrol of 20 mg/kg 2 hour prior to the administration of tartrazine 75 mg/kg. Rats’ urine was collected before and after treatment for 4 weeks. Level of F2-isoprostane was examined by using an 8-iso-PGF2α enzyme immuno assay kit. The comparative analysis of the pretest groups showed that there was no difference between the average levels of F2-isoprostane in both groups (5.45±0.62 ng/mL in P0 group vs 5.42±0.64 ng/mL in P1 group) (P > 0.05). Meanwhile, after treatment for 4 weeks, the average level of F2-isoprostane in the P0 group was significantly different from the P1 group (6.61±0.93 ng/mL vs 3.79±0.48 ng/mL) (P < 0.01). Analysis of the treatment effect showed a significant increase of F2-isoprostane level in the P0 group, and a significant decrease in the P1 group (P < 0.01). Conclusion: Oral administration of resveratrol could prevent urinary F2-isoprostane elevation in tartrazine-induced male Wistar rats (Rattus norvegicus).Keywords: tartrazine, resveratrol, F2-isoprostaneAbstrak: Tujuan penelitian untuk membuktikan pemberian resveratrol oral dapat mencegah peningkatan F2-isoprostan dalam urin tikus (Rattus norvegicus) Wistar jantan yang dipapar tartrazine. Jenis penelitian eksperimental dengan menggunakan pretest-posttest control group design. Subyek penelitian ialah 24 ekor tikus (Rattus norvegicus), galur Wistar, sehat, berumur 2-3 bulan, dengan berat badan 200-220 gr, dibagi menjadi 2 kelompok, masing-masing berjumlah 12 ekor tikus. Kelompok pertama (P0) ialah kelompok kontrol, diberikan tartrazine 75 mg/kg BB dan 2 jam setelahnya diberikan plasebo berupa aquadest 2 ml. Kelompok kedua (P1) ialah kelompok perlakuan, diberikan tartrazine 75 mg/kg BB dan 2 jam setelahnya diberikan resveratrol 20 mg/kg BB. Saat sebelum dan sesudah perlakuan selama 4 minggu, urin tikus dikoleksi untuk pemeriksaan kadar F2-isoprostan menggunakan 8-iso-PGF2α enzyme immuno assay kit. Analisis komparasi sebelum perlakuan (pretest) menunjukkan rerata kadar F2-isoprostan pada kedua kelompok tidak berbeda nyata (5,45±0,62 ng/mL vs 5,42±0,64 ng/mL) (P > 0,05). Setelah perlakuan selama 4 minggu, rerata kadar F2-isoprostan pada kelompok P0 berbeda nyata dibandingkan kelompok P1 (6,61±0,93 ng/mL vs 3,79±0,48 ng/mL) (P < 0,01). Analisis efek perlakuan menunjukkan terjadi peningkatan kadar F2-isoprostan pada kelompok P0 dan penurunan bermakna pada kelompok P1 (P < 0,01). Simpulan: Pemberian resveratrol oral dapat mencegah peningkatan F2-isoprostan urin tikus (Rattus norvegicus) Wistar jantan yang dipapar tartrazine.Kata kunci: tartrazine, resveratrol, F2-isoprostan, urin